KHOJA AHRAR WALI IN THE MENTIONS OF ABDURAKHMAN JAMI AND ALISHER NAVOI (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the life and work of Khoja Ubaidullo Ahror (1404-1491), a prominent figure of the Naqshbandi order, based on the works of Abdurahman Jami and Alisher Navoi, as well as medieval sources. Khoja Ahror was one of the prominent leaders of the Naqshbandi order, as well as the largest political figure and owner of one of the largest fortunes of his time. His name is closely associated with the intensification of the political and economic activities of the Naqshbandi order and the spread of its ideology beyond the borders of Central Asia.